PENGARUH MODEL PEMBELAJARAN KOOPERATIF BERBANTUAN MEDIA KARTU KUARTET TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR MATERI PENERAPAN SIKAP SESUAI SILA PANCASILA - Mutia Sari, Indi; Noviana, Eddy; Munjiatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of elementary school students in Pancasila Education, particularly on the topic of implementing attitudes in accordance with the principles of Pancasila. The purpose of this study was to determine the effect of a cooperative learning model assisted by quartet card media on students' learning outcomes. This research employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The research subjects were 31 grade IV C students at State Elementary School 188 Pekanbaru. Data were collected through pretest and posttest instruments in the form of multiple-choice questions. The data were analyzed using normality tests, paired sample t-tests, and N-Gain analysis. The results showed that the mean pretest score was 46.45, which increased to 68.38 in the posttest. The paired sample t-test yielded a significance value of 0.000 (< 0.05), indicating a significant effect of the treatment on students' learning outcomes. Furthermore, the N-Gain score was 0.39, which falls into the moderate category. Therefore, it can be concluded that the cooperative learning model assisted by quartet card media has a positive and significant effect on improving elementary school students' learning outcomes in learning the implementation of attitudes in accordance with the principles of Pancasila.